Sero-molecular prevalence of toxoplasmosis in hemodialysis and peritoneal dialysis patients in Markazi Province, Iran - Hossein Sarmadian; Mana Shojapour; Fereshteh chegeni; Mohammad Amin Tabatabaiefar; Farshid Haghverdi; Roham Sarmadian; Reza Ghasemikhah (Tropical Medicine and Health)
Abstract Background Infectious diseases, particularly parasitic infections such as toxoplasmosis, contribute significantly to the morbidity and mortality of hemodialysis patients. Toxoplasma gondii infection poses serious risks, especially to immunocompromised individuals. This study aimed to assess the prevalence of latent toxoplasmosis in dialysis patients in Markazi Province, Iran. Methods A total of 181 patients (168 hemodialysis and 13 peritoneal dialysis) were included in this cross-sectional study. Blood samples were collected and tested for anti-Toxoplasma IgG and IgM antibodies using ELISA, while PCR was used to detect T. gondii DNA. Data were analyzed using SPSS, with P < 0.05 considered significant. Results Out of 181 patients, 123 (67.95%) were seropositive for IgG antibodies, with the highest prevalence in those aged over 60 years. No cases tested positive for IgM antibodies or T. gondii DNA. Age was significantly associated with higher seroprevalence (P < 0.05), but there were no significant differences regarding gender, dialysis type, or duration of dialysis. Conclusion The high prevalence of latent toxoplasmosis in dialysis patients underscores the need for regular screening to prevent serious complications. Given the limitations of serological tests, molecular diagnostics like PCR should be considered for better detection in immunocompromised patients.